Assessment of environmental health based on a complementary approach using metal quantification, oxidative stress and trophic ecology of two gull species (Larus michahellis & Larus audouinii) breeding in sympatry. (October 2020) - Laranjeiro, Maria I.; Alves, Luís M.F.; Silva, Joana M.; Calado, Joana G.; Norte, Ana C.; Paiva, Vítor H.; Lemos, Marco F.L.; Ramos, Jaime A.; Novais, Sara C.; Ceia, Filipe R.
Abstract: Metal pollution is currently a major issue in marine ecosystems, as organisms, and particularly seabirds, are exposed and accumulating increased levels from several anthropogenic sources. A set of 13 metals were quantified in two gull species breeding in sympatry, and in two distinct colonies separated by ca. 400 km. Oxidative stress was measured, and stable isotope analyses were used to link metal contamination and oxidative stress with the trophic ecology of each species/population. There was a clear segregation of metal contamination between the two species and to a much lesser extent between colonies. Overall, Audouin's gull was the most contaminated species for most metals, once this species relies mainly on fish and other marine resources. The Yellow-legged gull feeds regularly on terrestrial food sources besides fish, which may dilute contamination levels. Oxidative stress responses were related with birds' trophic ecology and foraging habitat, but apparently not with metal contamination. Graphical abstract: Unlabelled Image Highlights: Metal contamination was assessed in two gull species and from two distant colonies. Oxidative stress responses and stable isotopes (SI) were measured in all seabirds. Clear differences in metals between the two species, but not between colonies Relationships between SI and both metals and oxidative stress were found. Oxidative stress responses were driven by specific diets of each species and colony.